2002
DOI: 10.1007/s00436-002-0688-2
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of different Leishmania mexicana morphotypes with plasminogen

Abstract: The interaction of plasminogen with Leishmania mexicana promastigotes was found, using immunoperoxidase assays, to occur with a specific morphotype. In in vitro cultured promastigotes, the morphotype that possessed the plasminogen binding capacity had round to ovoid cell bodies. In contrast, neither slender nor metacyclic promastigotes showed this property. In vivo plasminogen immunofluorescence assays showed deposits of plasminogen exclusively on the cell surface of promastigotes. This was observed as intense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…As plasminogen binds L. mexicana enolase in vitro, we examined the inhibition of plasminogen binding in vivo on the surface of the parasite by anti-L. mexicana enolase antibodies to evaluate the contribution of enolase on binding. For these experiments parasites that had received a heat shock were used as it had been demonstrated that the parasites having round shapes that are generated after this treatment bind more plasminogen than those with slender shapes (Calcagno et al 2002). The association of plasminogen with L. mexicana cells was tested by incubating these parasites with plasminogen and BSA in the presence or absence of the antibody, washing them thoroughly, incubating them in the presence of a plasminogen activator, and finally adding the plasmin chromogenic substrate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As plasminogen binds L. mexicana enolase in vitro, we examined the inhibition of plasminogen binding in vivo on the surface of the parasite by anti-L. mexicana enolase antibodies to evaluate the contribution of enolase on binding. For these experiments parasites that had received a heat shock were used as it had been demonstrated that the parasites having round shapes that are generated after this treatment bind more plasminogen than those with slender shapes (Calcagno et al 2002). The association of plasminogen with L. mexicana cells was tested by incubating these parasites with plasminogen and BSA in the presence or absence of the antibody, washing them thoroughly, incubating them in the presence of a plasminogen activator, and finally adding the plasmin chromogenic substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, plasminogen regulates the expression of enolase in both fibroblast and peripheral blood mononuclear cells (Sousa et al 2005). As it has been demonstrated that L. mexicana is able to bind plasminogen (Avilán et al 2000;Calcagno et al 2002) and as this interaction contributes to the virulence of the parasite (Maldonado et al 2006), we tested the possibility that enolase at the surface of this parasite is also a plasminogenbinding protein. The present study shows that purified recombinant enolase is able to bind plasminogen in a lysine-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suggested functions for plasmin in pathogenic infection include extracellular matrix protein degradation, fi-brin degradation, release of peptides for nutrition, and metalloprotease activation. Since the ability to interact with plasminogen has been shown in a trypanosomatid, Leishmania mexicana (Avilan et al 2000, Calcagno et al 2002, we explored, in this work, the plasminogen binding ability of T. cruzi.…”
mentioning
confidence: 99%
“…Hamster footpad lesions were used as sources of amastigotes for isolation and for maintenance of the parasites. An amastigotes-enriched preparation was obtained from the lesion as described elsewhere (Calcagno et al 2002).…”
Section: Growth Of L Mexicanamentioning
confidence: 99%